Patient attitude and determinants toward chronic diseases control: A cross-sectional survey in rural China - Lu, Yuanyuan; Zhao, Yuhang; Shangguan, Xiaofang; Lv, Benyan; Huang, Rui (Frontiers in Public Health, 2022)
explore the determinants of patients’ attitude and satisfaction. Methods: A total of 844 patients in rural areas of Shandong, Henan, and Sichuan provinces with hypertension or diabetes were randomly selected for investigation. The outcome variables were the patients’ attitude and satisfaction toward chronic diseases control, which were measured through patient self-reported. Binary logistic regression models were used to explore the determinants of patients’ attitude and satisfaction. Results: Teachers were more likely to regard that chronic diseases management was helpful in their chronic diseases control than that in farmers (OR = 3.994, 95% Confidence Interval (CI) =1.309-12.188). Moreover, the probability of health institution recording chronic diseases changes and guiding rehabilitation for patients regularly is considered helpful 2.688 times more than those that are not. In addition, receiving chronic diseases management services can make patients repute that chronic diseases management services are helpful in controlling chronic diseases more capably (OR = 1.582, 95% CI =2.198-10.771). In terms of satisfaction, patients who do not know regular follow-up tend to be dissatisfied with chronic diseases control result(OR = 0.376, 95% CI =0.192-0.737; OR = 0.592, 95%CI =0.417-0.841). Conclusion: The government increases the promotion of chronic diseases management in rural areas to improve patients’ awareness. Health institutions also can provide diversified services to meet the needs for more people. At last, paying more attention to the timeliness of health services need to be considered to develop a health plan.